1962
DOI: 10.1071/ar9620960
|View full text |Cite
|
Sign up to set email alerts
|

The hair follicle population of cattle in relation to breed and body weight

Abstract: Hair follicle densities were studied in 330 cows sampled once, and 460 calves sampled twice at different ages. The calves were sampled at times varying in 2-month steps between birth and 22 months of age. Follicle density on the midside decreased with increasing body weight within animals according to a power of body weight very close to two-thirds. It is shown that data on follicle density, even from animals in the same environment sampled at the same age, are of little comparative value because of difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
5
1
1
Order By: Relevance
“…For example, skin thickness and sweat gland size are greater in the adult animal (Schotterer 1932;Hafez, Badreldin, and Shafei 1955) while hair density is less (Carter and Dowling 1954;Turner, Nay, and French 1962). However, although such age differences occur between young and adult animals, it would seem from the present results that the skin measurements do not vary appreciably with age in cattle over 2 years old.…”
Section: Discussion (A) Effect Of Agecontrasting
confidence: 50%
See 1 more Smart Citation
“…For example, skin thickness and sweat gland size are greater in the adult animal (Schotterer 1932;Hafez, Badreldin, and Shafei 1955) while hair density is less (Carter and Dowling 1954;Turner, Nay, and French 1962). However, although such age differences occur between young and adult animals, it would seem from the present results that the skin measurements do not vary appreciably with age in cattle over 2 years old.…”
Section: Discussion (A) Effect Of Agecontrasting
confidence: 50%
“…The present findings, however, differ from those of Barker and Nay (1964) who, in a study of 285 adult Jerseys, found that sweat gland size increased with age. Hair density has been shown previously to vary considerably with age and with body weight (Turner, Nay, and French 1962) and the effect of age is important up to the age of 3 years (Carter and Dowling 1954).…”
Section: Discussion (A) Effect Of Agementioning
confidence: 99%
“…Isto poderia dever-se ao fato de que o número de folículos por unidade de área diminuí com a idade (Turner et al, 1962), devido ao crescimento e expansão da epiderme, sem alteração no número de folículos. Todavia, é importante destacar que, quanto menor o número de pêlos por unidade de área, mais facilmente o vento penetra na capa, removendo o ar aprisionado entre os pêlos e favorecendo a transferência térmica.…”
Section: Tabela 1 -Médias Das Características Morfológicas Do Pelame unclassified
“…Breeds and strains which are better able to control body temperature have the largest glands. Zebu cattle and their crossbreeds have been shown to have higher follicle density than British-breed animals (Nay and Hayman 1956;Turner, Nay, and French 1962), although Pan (1963) found no significant difference between Jersey and Sahiwal cows. Pan, Donegan, and Hayman (1969) showed there was a positive correlation between the density of a sweat gland population in a body region and its sweating rate.…”
Section: Introductionmentioning
confidence: 99%